Two genera Campyloneurus Szépligeti and Iphiaulax Foerster in China, with the descriptions of fourteen new species (Hymenoptera, Braconidae, Braconinae) - Li, Yang; Achterberg, Cornelis Van; Chen, Xue-Xin (Zootaxa, 2020)
The species of the genus Campyloneurus Szépligeti and Iphiaulax Foerster (Hymenoptera, Braconidae, Braconinae) from China are revised and 32 species are recognized, including 14 new species (Campyloneurus brachyurus sp. nov., C. lasiofacialis sp. nov., C. longitergum sp. nov., C. longitudinalis sp. nov., C. micromacularis sp. nov., C. nigriventris sp. nov., C. promiscuus sp. nov., C. pachypus sp. nov., C. quadraticeps sp. nov., C. robusticella sp. nov., C. rugifacialis sp. nov., C. stigmosus sp. nov., C. tergipunctatus sp. nov. and Iphiaulax longinervis sp. nov.), which are described and fully illustrated. Campyloneurus kirbyi (Cameron, 1905) is reported from China for the first time. A key to taxonomically similar genera, Campyloneurus, Craspedolcus Enderlein, Cyanopterus Haliday, Iphiaulax and Maculibracon Li, van Achterberg & Chen), and a key to the Chinese species of the genera Campyloneurus and Iphiaulax are provided.